Adolescent Social Norms and Alcohol Use: Separating Between‐ and Within‐Person Associations to Test Reciprocal Determinism. (25th March 2019) - Meisel, Samuel N.; Colder, Craig R.
Abstract : Despite perceived drinking norms being robust predictors of adolescent alcohol use, few studies have assessed the development of perceived norms across adolescence and processes accounting for the strong associations between perceived norms and drinking. Using reciprocal determinism as a theoretical basis for understanding the development of adolescent drinking norms, this study examined reciprocal associations across nine waves of data spanning early to late adolescence. Bivariate latent curve models with structured residuals demonstrated consistent within‐person reciprocal associations between descriptive and injunctive norms and alcohol use after accounting for growth in norms and alcohol use. Results suggest the need for developmentally informed intervention efforts targeting perceived drinking norms during early and middle adolescence.